Semiconducting boron carbides with better charge extraction through the addition of pyridine moieties. (4th August 2016) - Echeverria, Elena; Dong, Bin; Peterson, George; Silva, Joseph P; Wilson, Ethiyal R; Driver, M Sky; Jun, Young-Si; Stucky, Galen D; Knight, Sean; Hofmann, Tino; Han, Zhong-Kang; Shao, Nan; et al.
Abstract: The plasma-enhanced chemical vapor (PECVD) co-deposition of pyridine and 1, 2 dicarbadodecaborane, 1, 2-B10 C2 H12 (orthocarborane) results in semiconducting boron carbide composite films with a significantly better charge extraction than plasma-enhanced chemical vapor deposited semiconducting boron carbide synthesized from orthocarborane alone. The PECVD pyridine/orthocarborane based semiconducting boron carbide composites, with pyridine/orthocarborane ratios ~3:1 or 9:1 exhibit indirect band gaps of 1.8 eV or 1.6 eV, respectively. These energies are less than the corresponding exciton energies of 2.0 eV–2.1 eV. The capacitance/voltage and current/voltage measurements indicate the hole carrier lifetimes for PECVD pyridine/orthocarborane based semiconducting boron carbide composites (3:1) films of ~350 µ s compared to values of  ⩽35 µ s for the PECVD semiconducting boron carbide films fabricated without pyridine. The hole carrier lifetime values are significantly longer than the initial exciton decay times in the region of ~0.05 ns and 0.27 ns for PECVD semiconducting boron carbide films with and without pyridine, respectively, as suggested by the time-resolved photoluminescence. These data indicate enhanced electron–hole separation and charge carrier lifetimes in PECVD pyridine/orthocarborane based semiconducting boron carbide and are consistent with the results of zero bias neutron voltaic measurements indicating significantly enhanced charge collection efficiency.